A Study on the Functional Role of the Locus Coeruleus in Memory Formation and Alzheimer's Disease - Luckey, Alison Michelle (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2022)
Over the past decade, the locus coeruleus (LC) has fast become a key instrument of study, resulting in a growing amount of evidence signifying its prominence and influence within the central nervous system. Moreover, the breakdown of the locus coeruleus-noradrenergic mechanism has been implicated in neurodegenerative and psychiatric disorders and may play a punitive role in the manifestations of these disorders. Therefore, to contribute to a deeper understanding of the locus coeruleus-noradrenaline (LC-NA) system, this thesis has two primary objectives of research: (1) to investigate the role of the LC in memory via validating the mechanistic evaluation of how (i.e., direct vs. indirect) and determining when (i.e., immediate vs. offline) non-invasive electrical stimulation affects neural circuits, and (2) to examine the role of the LC in Alzheimer’s disease (AD) by way of putting forth a new hypothesis that has identified and integrated characteristics in the LC-NA system in females that distinctly spotlight their precarious nature to disproportionately developing AD. Recent investigations have begun to assess the clinical significance of therapeutic non-invasive brain stimulation techniques to modify neuroplasticity and upregulate neuronal excitability in different neurological conditions, including memory deficits. The current thesis was built upon an existing proposal that employs non-invasive transcutaneous electrical stimulation of the greater occipital nerve (NITESGON) to activate the LC-NA pathway to enhance memory performance. Findings presented here provide evidence for the involvement of NITESGON using alternating current (AC) to generate an immediate effect during memory encoding presumptively via increased attention, whereas NITESGON utilizing direct current (DC) elicits an offline effect transpiring during the consolidation of information in both healthy, young and older adult populations. Additionally, further exploration regarding NITESGON’s effect during the consolidation phase resulted in findings that lend support to the behavioral tagging (BT) hypothesis, such that a learning event within a short time period of an additional independent novel event or stimuli will be more likely to convert to long-term memory (LTM), and therefore suggests that the application of NITESGON can be administered within a window of opportunity to promote memory stabilization. Taken together, the results presented demonstrate the LC’s prominent role in providing favorable effects on strengthening memory when targeted by NITESGON and offers substantial evidence to further propel the interest and growing body of non-invasive stimulation research forward. Research on enhancing and preserving human memory, such as the research performed above, has increased primarily due to AD's prevalence and inexorable conditions. Upon review of AD literature, it was apparent that the involvement of the LC-NA system and sex differences are two of the most rapidly emerging topics. To date, current literature either investigates the LC, due to it being one of the first brain areas to develop AD pathology, or acknowledges the neuroprotective effects of estrogens and how the loss of these female hormones have the capacity to contribute to the sex differences seen in AD; however, existing research has neglected to examine these two rationales concurrently. Reflecting upon previous literature led to a reevaluation of the approach taken in regards to female vulnerability to AD and put forth a new hypothesis considering how sex differences in the LC-NA structure and function could account for why females are more likely to develop AD, specifically, LC morphology, the paucity of estrogens, neuroinflammation, blood-brain barrier (BBB) permeability, apolipoprotein ε4 polymorphism (APOE ε4), and cognitive reserve. Collectively, the theoretical perspective presented aims to assist in alleviating current challenges surrounding female AD by providing thought-provoking connections into the interrelationship between the disruption of the female LC-NA system, the decline of estrogens, and AD vulnerability.
APPROVED
Keywords: Behavioral tagging; Associative memory; Peripheral nerve stimulation; Consolidation; Noradrenaline; Non-invasive brain stimulation